Principles of Raptor Cage Design - Moore, Adele (Wildlife Rehabilitation Bulletin, 2014)
Constructing a cage for raptors in rehabilitation requires planning to ensure the cage will have all the components required for training raptors and for a successful release back into the wild. The author explores a checklist of what is needed both in the planning and in the construction stages. TreeHouse just designed and completed a Raptor Rehabilitation Complex in which all the cage elements are under one roof and flexible.